Fullerol improves seed germination, biomass accumulation, photosynthesis and antioxidant system in Brassica napus L. under water stress - Xiong, Jun-Lan (Plant physiology and biochemistry : PPB, 2018)
Copyright © 2018. Published by Elsevier Masson SAS.